ANALISIS KELAYAKAN DAN UPAYA PENGEMBAGAN USAHA INDUSTRI TAHU DI KOTA PONTIANAK, KALIMANTAN BARAT - B01108081, FERNANDO TRIVELLY (Jurnal Curvanomic, 2014)
This research entitled â€œAnalisis Kelayakan Usaha Dan Upaya Pengembangan Usaha Industri Tahu Di Kota Pontianak Kalimantan Baratâ€. The results of processing data which used a feasibility analysis of business development tofu industry obtained Net Present Value (NPV) isÂ  Rp 449.701.619 (positive), Internal Rate of Return (IRR) is 69% (greater than 15% discount rate), and Benefit / Cost Ratio (B / C ratio) is 3,47. Strategies undertaken for the development of tofu industry based products processing, that is through the increase in quality of the product, where there are quality of raw materials, human resources, quality standards are used and the processing technology. The partnership with other businesses as well as increased use of technology access. Keywords: analysis of feasibility, industry of tofu, strategy of business development, tofu